Kuasa Eksklusi dalam Pembangunan Geothermal di Desa Ulubelu, Kecamatan Golewa, Kabupaten Ngada - Andriana Natalia Wea; Laurensius P.Sayrani; Yonatan H.L Lopo (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The research with the title Power Of Exclusion in Geothermal Development in Ulubelu Vilage,Golewa District, Ngada Regerency is motivated by the development of the Mataloko Georhermal Power Plant (PLTPB) with a formulation of How the power of exclusion is Particed Regarding Regulation,coercion, markets and legitimacy in the dimensions of power John Gaventa with the aim of exsplaning the practice of exclusionary power,in order to differentiate this proposal, the researcher used Tania Muray Lii research theory of exclusionary power by elaborating on John Gaventa three dimensional theory of power. The research method used in writing this proposal is descriptive qualitative. The research method used in this research is in the form of excluded local communities in the case limiting community access to land and natural. Resources project regulations energy as a central government initiative and regional government support and coercive power as an exclusionary strategy as well as the market as e vehicle for exclusionand supported by legitimasi which is used as a mode of geothermal development. Resources project regulations energy as a central government initiative and regional government support and coercive power as an axclusionary strategy as well as the market as a vehicle for exclusion and supported by legitiasi which is used as a mode of the geothermal development. The complexcity of the power dynamics the occur and the interactions between various kinds of intersests in the power dynamics the occur in the context of geothermal development. The analysis uses lii (2011) social exclusion theory framework and John Gaventa (2006) 3 dimensional theory of power to provide an In depth understanding of exclusion that exixts in society. Not a few people have lost access to land and land and to agricultural land as well as the implementation of authotharian regulations without considering the local context. This research shows that even though geothermal energy is clean, the development procces can create or worsen social injustice if it is not managed well. The implicatins of these findings are the need for WKP policy reform that takes into account the right of indigenous peoples, fair compensation mechanisms and transparent decision making processes that involve the entire community as well as aducational programs to increase public understanding of community rights.